2019
DOI: 10.1016/j.jad.2018.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength and depression among 34,129 adults aged 50 years and older in six low- and middle-income countries

Abstract: HIGHLIGHTS Little is known about the relationship between handgrip strength and depression  Our data across 6 LMICs suggests weak handgrip strength is associated with depression.  Across all countries, weak handgrip strength was associated with a 1.45 (95%CI=1.12-1.88) times higher odds for depression.  Future research should seek to establish the predictive value of this inexpensive measure for clinical use.Abstract (250/250) Introduction: Handgrip strength is a simple and inexpensive marker of health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
65
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 68 publications
(39 reference statements)
11
65
2
Order By: Relevance
“…In a cross-sectional study that examined the relationship between physical activity and SRH, 6) https://doi.org/10.4082/kjfm.18.0200 95% CI, 1.12-1.88) times higher odds for depression after adjusting for potential confounders. 25) The results of these two studies are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In a cross-sectional study that examined the relationship between physical activity and SRH, 6) https://doi.org/10.4082/kjfm.18.0200 95% CI, 1.12-1.88) times higher odds for depression after adjusting for potential confounders. 25) The results of these two studies are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…52 Others have shown a correlation between grip strength and the Mini-Mental State Examination scores of geriatric inpatients, 53 information processing speed and executive functioning of patients attending a memory clinic, 54 Stroop Task and 6item Cognitive Impairment Test scores of physically active adults, 55 visual memory,and reaction time of patients with schizophrenia, 56 and Animal Fluency Test and Digital Symbol Substitution Test scores of cancer survivors. 57 A link between grip strength and depression has been demonstrated among residents of 6 low and middle income countries 58 as well as Brazil 59 and Korea. 60 Using a cutpoint of less than 30kg for men and 20kg for women for weak grip, Ashdown-Franks et al found a prevalence of depression of 8.8% among adults classified as weak versus 3.8% among adults not classified as weak.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 99%
“…60 Using a cutpoint of less than 30kg for men and 20kg for women for weak grip, Ashdown-Franks et al found a prevalence of depression of 8.8% among adults classified as weak versus 3.8% among adults not classified as weak. 58 Kyu-Man et al determined in a sample of older adults that the correlation between grip strength and depression was lower in older adults with a higher household income. 61 Perhaps the high income of Australians explains why Gopinath et al did not find their grip strength to be associated with depression.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 99%
“…Men (n = 1,209) Women (n = 1,443) P www.nature.com/scientificreports www.nature.com/scientificreports/ Multiple studies using various muscle strength indices have linked HGS with depressive symptoms among older adults. A cross-sectional study using data from the World Health Organization's study on Global Ageing and Adult Health showed that dynapenia was associated with depression risk in middle-aged and elderly adults from six low-and middle-income countries 15 . Among Asian populations, HGS has been significantly associated with depressive symptoms.…”
Section: Characteristicsmentioning
confidence: 99%
“…Given its predictive validity and simplicity, HGS could be a useful health-screening tool for older patients in primary care.Low HGS might cause poor mental health. Several studies have reported that low HGS was associated with an increased risk of depressive symptoms among older adults [15][16][17][18] . However, only one study has investigated the association between HGS and suicidal ideation, and it reported that low relative HGS was associated with suicidal ideation 19 .…”
mentioning
confidence: 99%